Current analytical methods to quantify PAHs in activated carbon and vegetable carbon (E153) are not fit for purpose. (15th September 2022) - Hilber, Isabel; Blum, Franziska; Schmidt, Hans-Peter; Bucheli, Thomas D.
Abstract: Pyrogenic carbonaceous materials (PCM) are increasingly used in a wide variety of consumer products, ranging from medicine, personal care products, food and feed additives, as well as drinking water purification. Depending on the product category and corresponding legislation, several terms are commonly used for PCM, such as Carbo activatus, C. medicinalis, vegetable carbon (E153), (activated) charcoal, (activated) biochar, or activated carbon. All PCM contain polycyclic aromatic hydrocarbons (PAHs) co-produced during pyrolysis. However, the actual PAH-content of PCM may range from negligibly low to alarmingly high depending on pyrolysis conditions and, if any, subsequent activation. Because of their health risk, PAHs need to be determined in many such PCM containing products, and concentrations are regulated by respective legally binding documents. Several such documents even specify the analytical method to be used. In this paper, we first argue that based on existing literature, currently legally binding methods to quantify PAHs in such products might not be fit for purpose. Secondly, we exemplarily determined PAH concentrations with a method previously optimized for biochar in a selection of 15 PCM or PCM-containing commercial products, illustrating that concentrations up to 30 mg kg −1 can be found. Consumer safety is of concern according to Swiss norms for drinking water and EU regulations for food additives for some of the investigated samples. In fact, some products would not have been allowed to be put on the market, if regulations with fit for purpose analytical methods existed. As PAHs were detected in considerable concentrations when extracted with toluene for 36 h, the authors suggest a corresponding adaption of existing methods and harmonization of the legislation. Graphical abstract: Image 1 Highlights: Many consumer products contain or consist of pyrogenic carbonaceous materials (PCM). PCM can contain polycyclic aromatic hydrocarbons (PAHs). Regulated analytical methods for PAHs in PCM are not fit for purpose. Considerable PAHs concentrations were found in properly analysed consumer products. Laws concerning PAHs in PCM of consumer products should be adapted and harmonized.